PENERAPAN MODEL PENUGASAN (ASSIGNMENT MODEL) HUNGARIAN UNTUK OPTIMALISASI ALOKASI JADWAL KHOTBAH PENATUA GUNA MEMINIMALKAN INDEKS KESENJANGAN KONTEKSTUAL: (Studi Operasional Manajemen Pelayanan Liturgi Berbasis Komputasi QM for Windows) - Refani Abednego Samosir; Jhon Kristopel Manalu; Parapat Gultom (Kampus Akademik Publiser, 2026)
Optimization of the assignment of ministers of the Word (Preachers) across various categorical worship services constitutes one of the strategic responsibilities of the Congregational Leadership to ensure the relevance of theological messages and the fulfillment of the congregation's spiritual needs. This study aims to determine the optimal assignment combination of four Elders/Preachers (Preacher 1, Preacher 2, Preacher 3, and Preacher 4) to four specific categorical worship positions (General/Adult Worship, Youth/Young Adult Worship, Sunday School/Children's Worship, and Men's/Elderly Worship) at GMI. A quantitative approach was applied through the Assignment Model with the minimization criterion of the